2019
DOI: 10.3390/ma12142267
|View full text |Cite
|
Sign up to set email alerts
|

Emission Enhancement of Cu-Doped InP Quantum Dots through Double Shelling Scheme

Abstract: The doping of transition metal ions, such as Cu+ and Mn2+ into a quantum dot (QD) host is one of the useful strategies in tuning its photoluminescence (PL). This study reports on a two-step synthesis of Cu-doped InP QDs double-shelled with ZnSe inner shell/ZnS outer shell. As a consequence of the double shelling-associated effective surface passivation along with optimal doping concentrations, Cu-doped InP/ZnSe/ZnS (InP:Cu/ZnSe/ZnS) QDs yield single Cu dopant-related emissions with high PL quantum yields of 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…We conducted 8 new syntheses of InP QDs to test the prediction accuracy of our models. The experiments were designed based on four procedures found in the literature [40][41][42][43] with minor adjustments such that all reaction parameters were not already included as entries in the dataset used to train the machine learning models. The reaction parameters were also selected such that they were not easily extrapolated from the parent procedures.…”
Section: Synthesesmentioning
confidence: 99%
“…We conducted 8 new syntheses of InP QDs to test the prediction accuracy of our models. The experiments were designed based on four procedures found in the literature [40][41][42][43] with minor adjustments such that all reaction parameters were not already included as entries in the dataset used to train the machine learning models. The reaction parameters were also selected such that they were not easily extrapolated from the parent procedures.…”
Section: Synthesesmentioning
confidence: 99%
“…Kim et al reported a maximum Photoluminescence Quantum Yield (PLQY) of 57−58% with optimal Cu doping in InP QDs having double shelling. 46 However, usually the Cu and Mn ions form radiative centers with no optical filtering for monochromaticity of light. However, silver, belonging to Group I of the Periodic Table and having a nonradiative center, can be used as an efficient nontoxic dopant material that can suppress trap emission of the shell layer and show an optical filtering effect, producing monochromatic light emission.…”
Section: Introductionmentioning
confidence: 99%
“…Metal ions such as Cu + , and Mn 2+ have been widely explored as suitable dopants in QDs. Kim et al reported a maximum Photoluminescence Quantum Yield (PLQY) of 57–58% with optimal Cu doping in InP QDs having double shelling . However, usually the Cu and Mn ions form radiative centers with no optical filtering for monochromaticity of light.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue consists of four articles, and they cover a broad range of topics from synthesis and characterization of QDs to fabrication and study of operating mechanisms of QD devices. One of the articles is related to QD materials chemistry and QD-based EL devices [7]. Two articles then focus on QD-based photovoltaic devices [8,9], and the last article proposes a new driving mechanism for a QD device [10].…”
mentioning
confidence: 99%
“…Moreover, the team fabricated QLEDs where the synthesized Cu-doped InP QDs were incorporated. This article can serve as a good guide on how to improve the efficiency of heavy-metal-free QDs [7]. Moving to the articles concerning QD-based photovoltaics, Zhang et al presented a device architecture-modified phototransistor with improved performance where perovskite CsPbBr 3 QDs-ZnO QD film hybrids were employed.…”
mentioning
confidence: 99%